Occupational Therapy Practitioner Experiences Applying High-Intensity Rehabilitation: A Qualitative Analysis. - Pisegna, Janell; Hinrichs-Kinney, Lauren; Pontiff, Mattie; Beisheim-Ryan, Emma; Butera, Katie A.; Stevens-Lapsley, Jennifer (Physical & Occupational Therapy in Geriatrics, 2026)
Background: Rehabilitation is often underdosed for older adults with medical complexity in skilled nursing facilities (SNFs). This study sought to examine the perspectives of occupational therapy practitioners (OTPs) on applying high-intensity resistance and rehabilitation (HIR), an evidence-based therapeutic approach to functional strength training, in SNFs. Methods: OTPs (N = 16) at eight SNFs participated in focus groups during and following an 18-week HIR implementation program, guided by the Practical Robust Implementation and Sustainability Model. Results: Thematic analysis identified three themes related to OTPs' experiences applying HIR: 1) aligning HIR with occupation-based practice; 2) factors influencing HIR application and participation in the implementation program; and 3) recommendations to help OTPs apply HIR. Conclusions: This work identifies HIR's alignment with occupation-based and client-centered practice and how OTPs applied HIR among older adults with medical complexity in the SNF setting. This work also highlights the impact of OTP perspectives on the implementation of evidence-based practices.